Питер Пэн: сказочная повесть / Д. Барри - Барри Джеймс Мэтью (Репро, 1995)
Экземпляры: БС (20170227) / Инвентарный номер: РТШ48821 / Цена: 3600.00 / Сис.шифр: И(Англ) / Авт.знак: Б 25 / ГРНТИ: 17 / ББК: 84(4/8)